2017
DOI: 10.1177/1557988317743385
|View full text |Cite
|
Sign up to set email alerts
|

Foods, Dietary Patterns and Occupational Class and Leukocyte Telomere Length in the Male Population

Abstract: Telomeres contain TTAGGG repetitive sequences and are located at the end of human chromosomes. Telomere dysfunction is associated with some age-related and chronic diseases, but its relationship with foods, dietary patterns, and occupational class in the young male population is not yet known. In this cross-sectional study, 300 healthy men, residents of Tehran, aged 25–40 years were enrolled from January to December 2016. We employed a cross-sectional study of 300 healthy people, residents of Tehran, aged 25-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…To date, the results of the effect of fish consumption on TL remain controversial. The positive association between fish and a longer TL reported by Meshkani et al [ 29 ] is consistent with previous cross-sectional studies in the adult population [ 37 , 38 ] and one randomised controlled trial in patients with cardiovascular disease [ 39 ]. However, several observational studies with different designs found no association [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…To date, the results of the effect of fish consumption on TL remain controversial. The positive association between fish and a longer TL reported by Meshkani et al [ 29 ] is consistent with previous cross-sectional studies in the adult population [ 37 , 38 ] and one randomised controlled trial in patients with cardiovascular disease [ 39 ]. However, several observational studies with different designs found no association [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…Observational studies that have examined the association between telomere length and diet quality or dietary patterns that include or emphasise nut consumption have been performed in a range of different ethnic groups and countries, including Korea [ 27 ], China [ 36 , 37 ], Spain [ 38 , 39 ], Hong Kong [ 40 ], Italy [ 41 ], the United States [ 25 , 42 , 43 , 44 ], Iran [ 45 ], Australia [ 46 ], and Finland [ 47 ]. Of the fifteen observational studies, thirteen used a cross-sectional design [ 25 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], one study [ 27 ] used a prospective design, and one study included both a cross-sectional and prospective analysis [ 47 ]. Details of these studies can be found in Table 1 .…”
Section: Nut Consumption and Telomere Lengthmentioning
confidence: 99%
“…Here, nuts were combined with the food group of legumes, seeds and nuts. A further study among males in Iran showed that nuts and seed were negatively, albeit not statistically significantly, associated with telomere length [ 45 ]. It should be noted that participants in this study were younger (25–40 years) compared to most other studies in this area.…”
Section: Nut Consumption and Telomere Lengthmentioning
confidence: 99%
“…Higher cellular lipid level with acute and chronic inflammation causes changes in TL (Lee, Martin, Firpo, & Demerath, 2011; Rehkopf et al, 2016). Cellular inflammation and oxidative stress are reported to be associated with TL (Karimi et al, 2018; Rehkopf et al, 2016). In this condition, cell division capacity is highly increased and TL becomes too short in several stages of cell proliferation.…”
mentioning
confidence: 99%